Evaluating of psychiatric behavior in obese children and adolescents - Mohareri, Fatemeh; Noroozi Asl, Samaneh; Behdani, Fatemeh; Ghaemi, Nosrat (Iranian Journal of Child Neurology, 2018)
Abstract Introduction Obesity is a medical condition that it may have a harmful effect on health, leading to increased illness and reduced life expectancy. This study is aimed to evaluate the relationship of psychiatry disorders in overweight and obese children and adolescents. Methods In this was case-control study, one hundred and sixty child and Adolescent were recruited. The sampling method of this study was non-probability and biased. Study instruments were SDQ, CDI, STAI, Peds QL. All questionnaires were self-administrating that was completed by subjects or their parents. Differences between groups were examined using t-test and chi-square tests as appropriate. Results The results our study showed no significant different in scores of anxiety between two groups. But showed significant different in scores of depression, quality of life, and strength and difficult between two groups. Also there was no significant difference in gender effect on anxiety and Depression. However, in Quality of life test showed that emotional symptoms were more in girl than boys. In contrast, the conduct problems were more in boys than girls. Anxiety and Depression was more in adolescents than children Concussion Our study showed obesity has a negative effect on the anxiety, depression, and self-esteem of children and adolescents. It can be suggested that obesity might be a more important risk factor for depression, anxiety, and other psychiatry disorders. This study also emphasizes the importance of prevention of obesity.